Antimicrobial Stewardship Program: actions and education in Brazilian pediatric intensive care units - Eliane Carlosso Krummenauer; Mariana Portela de Assis; Mara Rubia Santos Gonçalves; Magda Machado de Miranda Costa; Rochele Mosmann Menezes; Fabio Araujo Motta; Jane Dagmar Pollo Renner; Marcelo Carneiro (Revista Latino-Americana de Enfermagem)
Objective: to evaluate the educational elements and actions of the Antimicrobial Stewardship Program (ASP) in Pediatric Intensive Care Units (PED-ICU) in Brazil. Method: this was a multicenter, prospective study carried out between October 2022 and January 2023, using an electronic form. Educational actions for professionals and patients on microbial resistance were analyzed, as well as interventions to improve prescribing, such as prospective audits, feedback and pre-authorization. The data was grouped by location, care profile and number of beds and analyzed using parametric and non-parametric statistical methods. Results: of the 219 PED-ICUs with ASP in place, 44.7% were in the Southeast and 58.9% carried out continuing education for professionals. Only 6.8% promoted educational activities for patients and companions, concentrated in public hospitals with more than 200 beds. The education component showed weaknesses, especially in smaller hospitals, while actions to improve prescribing were more consolidated, with 70.8% implemented. Private hospitals and those in the Southeast and South stood out in terms of adherence to management practices. Conclusion: the study revealed significant disparities in the implementation of ASPs in Brazilian PED-ICUs, highlighting the need to strengthen continuing education and engage all those involved in order to increase adherence, reduce antimicrobial resistance and improve pediatric care.